2019
DOI: 10.1080/09540105.2019.1593325
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 2-mediated induction of avian β -defensin 9 by Lactobacillus rhamnosus and its cellular components in chicken intestinal epithelial cells

Abstract: This study aimed to investigate the effects of probiotic Lactobacillus rhamnosus MLGA and its cell wall components on the induction of avian β-defensin 9 (AvBD9) expression in intestinal epithelial cells (IECs) from chicken embryos and to elucidate the underlying mechanism. Chicken IECs were stimulated with L. rhamnosus MLGA or cell wall components. Quantitative RT-PCR analysis was used to determine the expressions of target genes. L. rhamnosus MLGA and its cellular components significantly induced AvBD9 and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Zhu et al [ 59 ] reported that the release of mBD-14 by mouse osteoblasts was mediated by the activation of p38 MAPK and NF-κB in response to S. aureus -secreted bacterial exoproducts. Jia et al [ 60 ] also confirmed that Lactobacillus rhamnosus MLG A , and its cell wall component, peptidoglycan, induced AvBD9 gene expression in chicken intestinal epithelial cells and that this was mediated by the TLR2-NF-κB/AP-1 signalling pathway, where TLR2-NF-κB constituted the main signalling axis. Results of this study showed that S.c up-regulated NF-κB and MAPKs signalling pathway molecules (NF-κB, p38, JNK and ERK1/2) at the mRNA level.…”
Section: Discussionmentioning
confidence: 94%
“…Zhu et al [ 59 ] reported that the release of mBD-14 by mouse osteoblasts was mediated by the activation of p38 MAPK and NF-κB in response to S. aureus -secreted bacterial exoproducts. Jia et al [ 60 ] also confirmed that Lactobacillus rhamnosus MLG A , and its cell wall component, peptidoglycan, induced AvBD9 gene expression in chicken intestinal epithelial cells and that this was mediated by the TLR2-NF-κB/AP-1 signalling pathway, where TLR2-NF-κB constituted the main signalling axis. Results of this study showed that S.c up-regulated NF-κB and MAPKs signalling pathway molecules (NF-κB, p38, JNK and ERK1/2) at the mRNA level.…”
Section: Discussionmentioning
confidence: 94%
“… 45 The role of TLRs and NLRs in mediating the induction of β-defensin expression by peptidoglycan or its fragments has been previously demonstrated. 34 , 46 48 In the present study, we showed that peptidoglycan hydrolysates (fragments) also promoted AvBD9 expression in PBMCs albeit at a lesser magnitude than intact peptidoglycan from L. rhamnosus MLAG. However, the inducible expression of AvBD9 by peptidoglycan hydrolysates was diminished in splenocytes as compared to intact peptidoglycan.…”
Section: Discussionmentioning
confidence: 51%
“…In a previous study we demonstrated that intact peptidoglycan from L. rhamnosus MLGA induces AvBD9 gene expression in primary chicken small intestinal epithelial cells in both time- and dose-dependent manners, with the maximal response occurring at 4 h post-stimulation at a concentration of 50 µg/ml. 34 To further examine whether L. rhamnosus MLGA-derived peptidoglycan is capable of stimulating AvBD9 expression in other cell types, especially immune cells, we performed both dose-response and time-course experiments in primary PBMCs, splenocytes, thymocytes, and hepatocytes. An obvious time-dependent increase in AvBD9 expression was elicited in PBMCs in response to treatment of 50 µg/ml peptidoglycan, peaking at 6 h post-stimulation and returning to the basal level after 48 h of incubation ( Figure 1a ).…”
Section: Resultsmentioning
confidence: 99%
“…Probiotic utilized TLR-2 signalling for the release of IL-10 from regulatory T-cells to induce immune tolerance response (Konieczna et al 2012). TLR-2 also played important role in induction of anti-microbial peptides which acted against the invasion of pathogens causing epithelial damage (Jia et al 2019). Moreover, present study also con rmed that probiotic L. rhmanosus maintains immunotolerance through decreasing the expression of TLR-4 even in the presence of E. coli.…”
Section: Discussionmentioning
confidence: 99%